Happiness in a time of rapid social change - Bernik, Ivan (Teorija in praksa, 2012)
In the paper we focus on some aspects of the distribution of happiness in Slovenia between 2000 and 2009, which can be characterised as a period of the gradual consolidation of major political and economic transformations. We hypothesise that, due to the gradual rise in economic prosperity and political stability in Slovenia, there was an increase in the level of happiness. Nevertheless, we also expect that due to the new social cleavages generated by the country's post-socialist transformation this period was characterised by a growing gap between the least and the most happy. We further expect that the social composition of the least and most happy parts of the Slovenian population changed considerably over the course of time. Yet none of these hypotheses are confirmed by our data. There were some oscillations in both the average level of happiness and the gap between the least and the most happy but no clear trends of change. There was also no change in the social composition of the most and the least happy. The data indicate that in Slovenia in the period under study the dynamic of happiness was largely unaffected by the outcomes of the country's post-socialist transformation.
Keywords: Happiness; Sreča; Družbene spremembe; Social change; Social welfare; Družbena blaginja; Postsocialism; Postsocializem; Slovenia; Slovenija; družba; society